The Effectiveness of Digital Marketing Towards SMEs: A Systematic Literature Review - Zamri, Nur Atiqah Binti; Abdul Rahim, Ramita; Norizan, Norsabrena Binti (Advances in Social Sciences Research Journal, 2024)
The adoption of digital marketing has become crucial for many organizations, particularly among SMEs, emerging as a key business element. This research aims to investigate the digital marketing strategies embraced by SMEs and their impact on these enterprises. Employing a Systematic Literature Review (SLR) method, 21 studies out of 132 meeting the search criteria are examined, with a focus on digital marketing practices. Through this analysis, 17 factors are identified as the effects of digital marketing strategies on SMEs. Consequently, this paper serves as a valuable resource for organizations looking to implement digital marketing applications in SMEs. This systematic literature assessment explores the efficacy of digital advertising in enhancing the business performance of Small and Medium-sized Enterprises (SMEs). The study begins by highlighting the significance of SMEs in the business performance. It establishes a conceptual framework outlining the essential components of digital marketing practices within SMEs, encompassing aspects like website development, social media marketing, content marketing, email marketing, SEO, PPC advertising, and more. The investigation delves into various facets of digital advertising strategies, platforms, and tools utilized by SMEs, analyzing the key factors that influence SMEs in adopting digital marketing practices. Internal factors, such as digital marketing knowledge, organizational culture, resource allocation, and leadership support, are explored alongside external factors like market competition, technological infrastructure, government policies, and consumer behavior.